A Monetary-Fiscal Theory of Sudden Inflations - Marco Bassetto; David S Miller (The Quarterly Journal of Economics, 2025)
ABSTRACT This article posits an information channel as an explanation for sudden inflations. Households saving via nominal government bonds face a choice whether to acquire costly information about future government surpluses. They trade off the cost of acquiring information about the surpluses that back bond repayment against the benefit of a more informed saving decision. Through the information channel, small changes in the economic environment can trigger large responses in consumer behavior and prices. This setting explains why there can be long stretches of time during which government surpluses have large movements with little inflation response; then at some point, something snaps, and a sudden inflation takes off that is strongly responsive to incoming fiscal news.